1996
DOI: 10.1007/s002800051033
|View full text |Cite
|
Sign up to set email alerts
|

Application of interleukin 12 to antitumor cytokine and gene therapy

Abstract: In vivo administration of interleukin 12 (IL-12) at 2000 U/mouse induced IL-12-activated killer (IL-12AK) cells in parallel with an elevation in serum interferon-gamma (IFN-gamma) activity. Although NK1.1+CD3- natural killer cells are the major precursor of IL-12AK cells, asialoGM1+CD8+ T-cells were also demonstrated to be novel precursors. Such anomalous killer cells may play an important role in the early stages of the host defense mechanisms against tumors. It was also shown that IL-12 is effective in induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…1 IL-12 exerts a variety of biological effects on T and NK cells in vitro, 20 and its exogenous administration has been shown to have a dramatic effect on the suppression of tumor growth and metastasis. 8 Several investigations have described IL-12 gene transduction, [21][22][23][24][25][26][27][28][29] and some have shown that a tumor vaccine based on IL-12-transduced tumor cells is quite effective. We also demonstrated that irradiated RenCa secreting IL-12 suppressed the tumor growth of parental RenCa injected at contralateral sites, whereas irradiated parental RenCa did not.…”
Section: Discussionmentioning
confidence: 99%
“…1 IL-12 exerts a variety of biological effects on T and NK cells in vitro, 20 and its exogenous administration has been shown to have a dramatic effect on the suppression of tumor growth and metastasis. 8 Several investigations have described IL-12 gene transduction, [21][22][23][24][25][26][27][28][29] and some have shown that a tumor vaccine based on IL-12-transduced tumor cells is quite effective. We also demonstrated that irradiated RenCa secreting IL-12 suppressed the tumor growth of parental RenCa injected at contralateral sites, whereas irradiated parental RenCa did not.…”
Section: Discussionmentioning
confidence: 99%
“…These have included transfecting tumor cells with costimulatory molecules, 31,32 using dendritic cell (DC)-based vaccine therapy, 33-42 and transferring cytokines or cytokine genes into the hosts. 43,44 Although successful induction of CD4 immune responses resulting in tumor rejection has been widely reported, it is less clear whether such immune responses are able to protect against re-emerging tumor cells once the acute response has terminated and T cells have differentiated to resting memory cells.The aim of this study was to assess the contribution of CD4 T cells in different activation states in controlling tumor growth. For this, we made use of an experimental system previously described by us that allows the in vivo generation of pure effector or memory CD4 T cells from naive T-cell precursors.…”
mentioning
confidence: 99%
“…Furthermore, IL-12 gene transfer induced a T H1 response and generated a strong antitumor immunity. [7][8][9][10][11][12][13][14][15][16] IL-12 is a heterodimeric cytokine originally cloned from B lymphoblastoid cell lines. The cDNAs encoding the two IL-12 subunits are unrelated and encode for two distinct proteins which have molecular masses of 35 kDa and 40 kDa.…”
Section: Introductionmentioning
confidence: 99%